(untitled) (Federal University Gusau Faculty of Education Journal, 2026)
The study analysed the effect of Animal Traction Technology (ATT) on medium-scale maize farmers’ livelihood in Kaduna State, Nigeria. Cross-sectional survey design was adopted with multi-stage sampling procedure used to select 309 respondents out of 1573 medium-scale maize farmers across the four agricultural zones in Kaduna State. A structured questionnaire was used as instrument for data collection. The instrument was validated, pilot-tested giving a standardized reliability coefficient of 0.874. The instrument was administered to the respondents. Data collected was analysed using descriptive statistics in the form of frequency, percentages, mean and standard deviation. Logit regression analysis was used to test the null hypothesis. The finding showed that ATT in Kaduna State significantly affects maize farmers’ livelihood (p = 0.000 < 0.05). It was concluded that the life of medium-scale maize farmers was better after the use of ATT. The study recommends among others the need for Kaduna State Agricultural Development Agency (KADA) to integrate ATT into broader its livelihood improvement programmes to enhance the income and food security of farmers in the State.